Multi-Proxy Records of Late Holocene Flood Events From the Lower Reaches of the Narmada River, Western India - Sukumaran, Prabhin; Sant, Dhananjay A.; Krishnan, K.; Rangarajan, Govindan; Basavaiah, Nathani; Schwenninger, Jean-Luc (Frontiers in Earth Science, 2021)
Analyses of a fluvial sedimentary sequence from the lower reaches of the Narmada River establish a record of rhythmic cycles of sediment facies that represent floods during the late Holocene. The south-west Indian monsoon strongly influences the study area, and heavy rainfall or cyclones which originate from either the Bay of Bengal or the Arabian Sea, also affect the region. Optically stimulated luminescence dating places the 8 m thick sediment sequence in the climate transition phase which ranges from the Medieval Warm Period to the Little Ice Age. Multi-proxy analyses including high-resolution granulometry, magnetic susceptibility, ferromagnetic mineral concentration, facies major oxide geochemistry, and micro-fossil records (from two sedimentary units) are used to study these late Holocene flood events. The latter are characterized by multiple sediment facies, depositional events, changes in channel morphology, and distinctive flood signatures. Integration of these records enables to identify two distinct aggradations viz. phase I and phase II, as well as a relative change in channel morphology. The study describes eleven flooding events and their imprints over multi-proxy records. Historic documents and instrumental records from the town of Bharuch referring to floods, movement of channel sand, channel shallowing, and the dysfunction of the ancient port of Bharuch further validate the inferences drawn from the sedimentary sequence. The study exemplifies the need to use high resolution and multi-proxy studies to interpret paleoflood records and climate signatures in order to build archives of monsoonal rivers.